A Rare Case of Melanotic Schwannoma Occurred Intraosseous of Sacrum: A Literature Review. Issue 2 (1st December 2022) - Yan, Xiaobo; Wang, Keyi; Lin, Nong; Huang, Xin; Fu, YanBiao; Ye, Zhaoming
Abstract : Background: Melanotic schwannoma is a rare tumor when it occurs in the sacrum. Though it is mostly classified as benign, the prognosis is unpredictable due to the possibility of recurrence and metastasis. Here, we reported a case of intraosseous of sacrum with good results and reviewed the literature. Case Presentation: A 33‐year‐old male patient complained of low back pain and was discovered to have an obstruction at S2. Following the necessary imaging diagnosis, we treated the patient with piecemeal excision in conjunction with extended curettage, and the frozen biopsy revealed that the tumor was melanotic schwannoma. The intraosseous portion of the lesion was curettaged using high‐speed drill to enlarge the edge of curettage, and piecemeal excision for lesion within the sacral canal. After surgery, the patient received total 56Gy radiotherapy and frequent follow‐up. After 15 months follow‐up, there was no evidence of recurrence, and the nerve function was normal. Conclusion: Melanotic schwannoma that occurs intraosseous of the sacrum is extremely rare and lacks typical clinical manifestations; however it can be identified through careful pathological and imaging diagnosis. Intralesional extended curettage combined with radiotherapy can achieve a good local control with a satisfactory clinical effect in this rare disease. Abstract : We discussed our successful management of this challenging tumor with a focus on preoperative diagnosis, surgical approach, and histological consideration to provide guidance for future clinical management in melanotic schwannoma.